Legal Protection of Siri Wives Who Have Not Been Registered at the Dukcapil - Aura Fauziyyatur Rahma; Hardian Iskandar (Dinasti Research, 2024)
A siri marriage is a marriage carried out in accordance with Islamic law, but not officially recorded at the Office of Religious Affairs (KUA) or other government institutions. In other words, this marriage is valid religiously, but not recognized by state law. Siri marriages that are not registered in Dukcapil place wives in a vulnerable position to legal injustice. This research aims to find out and examine the legal protection for Siri wives who have not been registered in Dukcapil. This research is a type of normative legal research. This research uses a statutory approach, this research also uses secondary and primary data so that the research results prove that it is based on law. This research shows that a form of legal protection for unregistered wives can actually be included in one family but only records that the marriage has occurred. And in the KK there will be written the statement